Finding the Best Candidates: Innovations in Recruitment and Selection of Indonesian Army Soldiers - Aryanto, Ari; Claudia, Meiske (Jurnal Ilmiah Wahana Pendidikan, 2024)
Finding the best candidates is the key to building a strong TNI Army force. This article discusses innovations in the recruitment and selection of TNI Army soldiers to find the best candidates in the modern era. The innovation in the recruitment and selection of TNI Army soldiers is the implementation of online recruitment and selection. Prospective soldiers only need to register on the website, fill in the personal data form and wait for the validation results. After being declared to have passed validation, prospective soldiers can take various tests in the regions and if they pass, proceed to central level selection. Through online recruitment and selection, the regional reach becomes wider and opens up opportunities to recruit more competent TNI AD soldiers